INFLUENCE OF GRAIN REFINEMENT ON ANISOTROPY IN MECHANICAL PROPERTIES IN WROUGHT MAGNESIUM ALLOY AZ80 - Shahzad, M.; Qureshi, A. H.; Hussain, N.; Ali, L. (The Nucleus, 2011)
A direct-chill (DC) cast magnesium alloys AZ80 has been forward-extruded in a single pass with total degree of deformation (Ï† = 2.5) at two temperatures 200 Â°C and 350 Â°C. The as-extruded round profiles have been analyzed for microstructural changes i.e. degree of recrystallization and recrystallized grain size, using optical microscopy. The crystallographic texture has been measured from X-ray diffraction using Co KÎ± radiation. The results show that the extent of grain refinement increases with the lowering extrusion temperature. The crystallographic texture in both conditions consists of a predominant < 1010 > component accompanied by a relatively weaker < 1120 > component in the extrusion direction. Although, the crystallographic texture at both extrusion temperatures remains fairly similar, a fine grain size achieved at lower extrusion temperature reduces the degree of anisotropy in yield stress. A fine grain size inhibits the nucleation of tensile twins under compressive loading and gives a higher compressive yield stress, thereby lowering the anisotropy in yield stress.